Interferon-α counteracts the angiogenic switch and reduces tumor cell proliferation in a spontaneous model of prostatic cancer - Persano, Luca; Moserle, Lidia; Esposito, Giovanni; Bronte, Vincenzo; Barbieri, Vito; Iafrate, Massimo; Gardiman, Marina P.; Larghero, Patrizia; Pfeffer, Ulrich; Naschberger, Elisabeth; Stürzl, Michael; Indraccolo, Stefano; et al. (Carcinogenesis, 2009)
Interferon (IFN)-α is a cytokine with marked therapeutic activity in transplantable tumor models, that is in part due to angiogenesis inhibition. Aim of this study was to investigate the effects of IFN-α during the early phases of tumor development in the transgenic adenocarcinoma of the mouse prostate (TRAMP) model. To provide sustained IFN-α production, TRAMP mice were injected intraperitoneally with lentiviral vectors. IFN-α administration resulted in rapid and protracted upregulation of IFN-α-regulated genes associated with antiangiogenic and antiproliferative functions in the prostate of TRAMP mice, including guanylate-binding protein 1 (GBP-1), IFI204 and CXCL10-11. These transcriptional changes were accompanied by effects on the tumor vasculature, including significant reduction of intraductal microvessel density and increased pericyte coverage, and marked reduction of tumor cell proliferation, without induction of tumor necrosis. Intriguingly, GBP-1 and myxovirus resistance A, two IFN-regulated proteins, were found expressed in ∼40% of human prostate cancer samples analyzed, suggesting expression of endogenous IFN-α. Overall, these findings demonstrate that IFN-α is able to counteract the angiogenic switch and impairs tumor cell proliferation in preinvasive lesions. Since the angiogenic switch also marks progression of human prostatic cancer, these results highlight the potential of angiogenesis inhibitors for the development of chemoprevention strategies in high-risk individuals. © The Author 2009. Published by Oxford University Press. All rights reserved.
Created from Fastlane, Scopus look-up